Bright dipolar Bose-Einstein-condensate soliton mobile in a direction perpendicular to polarization - Adhikari, S. K. [UNESP] (American Physical Society (APS), 2014)
We demonstrate stable, robust, bright one-dimensional dipolar Bose-Einstein-condensate (BEC) solitons, moving in a direction perpendicular to the polarization direction, formed due to dipolar interaction for repulsive contact interaction. At medium velocity the head on collision of two such solitons is found to be quasielastic with practically no deformation. Upon small perturbation the solitons are found to exhibit sustained breathing oscillation. The findings are illustrated by numerical simulation using the three-dimensional mean-field Gross-Pitaevskii equation and a reduced two-dimensional model in three and two spatial dimensions employing realistic interaction parameters for a dipolar Dy164 BEC.